The transformations of Sino-Indian relations, 1950-2013 - Tseng, Lan-Shu (2017)
With or without global consent, China and India are the rising powers in Asia. After 1962, these two states have experienced enduring rivalries with historical and intricate hostility over the issues of territory, the sanctuary of Tibetan refugees on Indian territory, polarized relations with Pakistan, and geopolitical and resources competition. However, these disagreements have evolved from confrontation to the mixed elements of competition and cooperation to date. Sino-Indian relations have undergone a transformation with momentum toward cooperation on a number of regional and global issues over the last two decades.